Sound radiation from a roundabout - PIDDUBNIAK, Olexa; PIDDUBNIAK, Nadia (Archives of Acoustics, 2010)
Sound propagation from the vehicles moving on the city roundabout, with taking into account the wind is investigated. Solution of the problem for one moving sound source is found by means of the integral Fourier transforms extended over space variables and time. Inverse transforms are calculated approximately, using a stationary phase method and iterative technique. The solution for a general problem is obtained as a superposition of many partial solutions. The numerical analysis of noise characteristics is performed for the three-way Korfanty roundabout case in Łódź.